Alteration of phycobilisome excitation energy transfer properties in response to attenuations in peripheral electron flow - Guo, Zhanjun; Smolinski, Sharon L.; King, Paul W.; Lubner, Carolyn E. (Frontiers in Plant Physiology, 2024)
In Synechocystis sp. PCC 6803 (S. 6803), two types of phycobilisome (PBS) complexes, CpcG-PBS and CpcL-PBS, function to harvest light energy for photosynthetic reaction centers (RCs), photosystem I (PSI) and photosystem II (PSII). The compositional differences between these two forms of PBS and their specificity for RCs have led to suggestions that they may differ in function. To address this question, we examined how PBS-RC interactions, and the transfer of excitation energy from PBS to RCs, might be adjusted under conditions where electron demand and photon availability are modulated. The CpcG-PBS, CpcL-PBS, and RC complexes were isolated from a S. 6803 strain defective in expression of flavodiiron 1 (oxygen reduction reaction 1, ORR1) grown under varied light regimes. The energy transfer preference from CpcL-PBS to either PSI or PSII was investigated by in vitro crosslinking and 77 K fluorescence emission spectroscopy to assess energy transfer efficiency under photoexcitation. While the results demonstrate that the transfer of excitation energy from CpcL-PBS favors PSI over PSII in WT strains as previously shown, the preference of CpcL-PBS switches from PSI to PSII in ORR1 strains. Surprisingly, this change in preference was reproduced when ORR1 CpcL-PBS was crosslinked with WT RCs, or when WT CpcL-PBS was cross-crosslinked with ORR1 RCs, indicating there are physical modifications to both PBS and RCs that mediate the preference switch. In contrast, the analysis with ORR1 CpcG-PBS shows similar preferences to WT. Additionally, PBS populations in ORR1 shifted to a greater proportion of CpcL-PBS relative to CpcG-PBS. These results demonstrate that under conditions where electron utilization changes, there is a tuning of the excitation energy allocation from CpcL-PBS to RCs to manage the energy distribution for photosynthesis under dynamic flux conditions.